2017
DOI: 10.1177/1069397117697648
|View full text |Cite
|
Sign up to set email alerts
|

Testing Ethnological Theories on Prehistoric Kinship

Abstract: Although not a new topic, there is a growing trend in ethnology to interpret changing kinship terminology, social organization, and marriage practices deep into prehistory. These efforts are largely guided by phylogenetic, neoevolutionary, and historical particularist theoretical models using 19th to 20th century ethnographically recorded kin terminology. However, the "high-level" theoretical models and their assumptions are untestable without data dating to prehistory. Archeological kinship analysis based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…For example, of great interest are the correlations between the dwelling floor sizes and postmarital residence patterns detected by Melvin Ember (1973; see also Peregrine and Ember 2002), and further replicated and refined by Divale (1977), Brown (1987), Peregrine (2001), and Porčić (2010). However, the most sophisticated methodology for the identification of the basic features of the kin and family organization of ancient populations on the basis of the archeological data on ancient dwellings' characteristics and their patterns has been developed in the recent years by Bradley Ensor (2003Ensor ( , 2011Ensor ( , 2012Ensor ( , 2013aEnsor ( , 2013bEnsor ( , 2017.…”
Section: Fig 2 Identity Of Husband's Sister and Brother's Wife Withmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, of great interest are the correlations between the dwelling floor sizes and postmarital residence patterns detected by Melvin Ember (1973; see also Peregrine and Ember 2002), and further replicated and refined by Divale (1977), Brown (1987), Peregrine (2001), and Porčić (2010). However, the most sophisticated methodology for the identification of the basic features of the kin and family organization of ancient populations on the basis of the archeological data on ancient dwellings' characteristics and their patterns has been developed in the recent years by Bradley Ensor (2003Ensor ( , 2011Ensor ( , 2012Ensor ( , 2013aEnsor ( , 2013bEnsor ( , 2017.…”
Section: Fig 2 Identity Of Husband's Sister and Brother's Wife Withmentioning
confidence: 99%
“…Still, the International Workshop 'Murdock and Goody Re-visited: (Pre)history and evolution of Eurasian and African family systems' that was organized in April 2015 by the Max Planck Institute for Social Anthropology and whose papers have constituted the basis for a special issue of the Cross-Cultural Research (see, e.g., Ensor 2017;Souvatzi 2017) has demonstrated that we are close to having all the necessary ingredients to achieve a new breakthrough in the deep historical reconstruction, whereas Early Neolithic Greece and the Pontic steppes might be identified as ones of the possible springboards for such breakthroughs. Indeed, as has been shown above comparative linguistics and population genetics can potentially provide us with sufficient data to hypothesize about the language spoken by at least some of the populations of such places as Neolithic Greece or the Yamna culture area (including, naturally, the respective kinship terminologies).…”
Section: 'The Initial Farming Dispersal From Anatolia Broadly Equivamentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was positively received by archaeologists, as dwelling size is usually easy to determine, and has been applied to various archaeological contexts, e.g. to historical northern Iroquoian groups (AD 500-1300; [48]), Chaco Canyon region (AD 900-1150; [49][50][51][52]), Hohokam culture (AD 0-1450; [53,54]) and Neolithic Greece (6600/ 6500-3300 BC; [55]).…”
Section: Introductionmentioning
confidence: 99%
“…Since the time Hann wrote, the themes that Goody discussed and Goody's own contribution, have indeed received renewed attention. The revival has come partly from archaeologists and has owed a great deal to technical developmentsincluding new ways of assessing biological relatedness and place of origin from human remains (Ensor, Irish, and Keegan 2017), and inferring kinship structure and degrees of inequality from the relative sizes and arrangement of buildings (Ensor 2017;Kohler et al 2017). The renewed interest has also come from evolutionary anthropologists, who have pioneered 'phylogenetic' ways of projecting social arrangements back into the past, based on an analogy between linguistic change and the Darwinian development of separate but related species.…”
Section: Introductionmentioning
confidence: 99%